Probing heavy neutral resonances with preferential coupling to third generation fermions at the LHC (2023)
In this thesis a phenomenological feasibility of searching for heavy neutral mass resonances $Z'$ at the LHC is presented. In particular, this study considers a pair of two b-quarks as final states with non-universal fermion couplings in proton-proton collisions at $\sqrt{s}$=13 and 14 TeV. In the second part, we also present a search for heavy neutral mass resonances $Z'$ decaying into a hadronic tau and an electron with associated neutrinos. This search considers the neutral gauge boson with preferential coupling to third generation fermions using the full collected luminosity of 137 fb$^{-1}$ by the CMS detector of the LHC experiment.